Labour relations policies in multinational companies: A three-country study of power dynamics. (April 2015) - Lévesque, Christian; Bensusán, Graciela; Murray, Gregor; Novick, Marta; Carrillo, Jorge; Gurrera, Ma. Silvana
It is generally assumed that multinational companies will, to some extent at least, adapt their practices to host country environments. However, recent work suggests that this process of adaptation is yet more complex and uneven. It is our contention that subsidiary policy on labour relations is not simply the product of adaptation from and to home and host institutional environments but is in fact shaped by the multiple power relations that characterize multinational company subsidiaries. This three country comparison between Argentina, Canada, and Mexico shows that a policy of strong engagement with trade unions requires the presence of actors that can mobilize power resources. It is when both management and workers have power resources that subsidiaries are more likely to develop a policy of strong engagement with trade unions.